AB0657 Cyclophosphamide-sparing role of an intensified b-cell depletion protocol in anca-associated vasculitis: a case-control study. (12th June 2018) - Roccatello, D.; Fenoglio, R.; Rossi, D.; Radin, M.; Cecchi, I.; Murgia, S.; Baldovino, S.; Rubini, E.; Sciascia, S.
Abstract : Background: The management of ANCA-associated-vasculitis (AAV) requires the use of immunosuppressive drugs with potential toxicity. Recently, two trials demonstrated the efficacy of Rituximab (RTX) for the therapy of AAV. Objectives: this case-control study aims to evaluate the immunosuppressive-sparing effect of a RTX-based protocol compared to the standard CYC treatment. Methods: 26 patients with AAV and extracapillary glomerulonephritis were prospectively enrolled. Thirteen patients received an intensified protocol of B-cell depletion therapy (IBCDT) consisting of 4-weekly infusions of 375 mg/sm RTX followed by 2 infusions after 1 and 2 months, 3 pulses of methylprednisolone followed by prednisone tapered to 5 mg/day in three months and 2 pulses of 10 mg/kg CYC, without further maintenance therapy. Thirteen patients treated with 2 mg/kg/day CYC followed by azathioprine as a maintenance therapy served as controls. Results: A significant improvement (p<0.05) of B-VAS, ESR, CRP and ANCA was observed in the IBCDT-group at 3, 6 and 12 months, with decrease of mean creatinine values from 4.81±6.4 mg/dl to 2.21±3.8 mg/dl. When compared to controls, no difference was observed in terms of complete and partial response. However, the IBCDT regimen achieved a 1 g/month reduction of CYC cumulative dose (p<0.001). Conclusions: in the treatment of this sample of severe AAV patients, the IBCT protocol appeared to be noninferior to CYC-based regimen. Notably, the IBCDT regimen allowed a significant reduction of CYC cumulative dose. Disclosure of Interest: None declared